1993
DOI: 10.1007/bf00750571
|View full text |Cite
|
Sign up to set email alerts
|

The effect of crop residue and fertilizer use on pearl millet yields in Niger

Abstract: A bstract A field study was conducted over a 4-year period in Niger, West Africa, to determ ine th e effects of crop residue (CR), fertilizer, or a combination of crop residue and fertilizer (C R F) on yields of pearl millet (Pennisetum glaucum [L.] R. Br.). Despite a decline in yields of control plots (initial yields w ere 280 kg grain ha~J declining to 7 5 k g grain h a-1 over 4 years), yields of fertilizer plots were m aintained at 800-1,000 kg grain h a-1. Continued application of. CR slowly augm ented yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 15 publications
3
45
1
Order By: Relevance
“…Similar responses of enhanced C storage (up to 30 %) and increased yields (10-30 %) to residue management have also been found for, e.g., maize and soybean in the US (Wilhelm et al, 2004) and millet in Niger (Bationo et al, 1993).…”
Section: Trade-offs and Win-win Management Optionssupporting
confidence: 68%
“…Similar responses of enhanced C storage (up to 30 %) and increased yields (10-30 %) to residue management have also been found for, e.g., maize and soybean in the US (Wilhelm et al, 2004) and millet in Niger (Bationo et al, 1993).…”
Section: Trade-offs and Win-win Management Optionssupporting
confidence: 68%
“…With the emphasis on sustainable agriculture, attention has been increasingly turning to recycling of crop residues as a component of soil-fertility management programs in the tropical and semiarid tropical regions. The studies at ICRISAT Sahelian Center in Niger by Bationo et al (1993) and Hafner et al (1993) demonstrated that the addition of crop residue (millet straw) to a P-deficient acid sandy soil led to highly significant increases in P uptake and yield of pearl millet. The beneficial effect of crop residues on P uptake in these studies was attributed to the increased P mobility in soil as a result of millet straw addition (Kretzschmar et al, 1991).…”
Section: Introductionmentioning
confidence: 98%
“…Because of this, cultivation causes decrease in soil nutrients. Detailed studies on this chemical degradation of the soil (depletion of soil nutrients) and its recovery through fertilization have been conducted by A. Bationo, A. Buerkert, K. Hayashi and others (see Bationo and Mokwunye 1991;Bationo et al 1993;Buerkert et al 2000;Hayashi et al 2008;etc.). Additionally, Nakamura et al (2010) have published work on the depletion of soil organic matter as a result of cultivation and its recovery through the application of organic amendment.…”
Section: Preface -The Least Developed Countries In the Southern Saharmentioning
confidence: 99%